“It is necessary to dry (δέον αὐχμεῖν) the emotions” (Rep. 606d). Challenges from/to Plato (Circe de clásicos y modernos, 2022)
This article investigates a few passages from Plato’s Republic in order to uncover certain assumptions and consequences of the philosopher’s argument about the status of emotions, which culminates in the incisive and radical statement in book X, “It is necessary to dry the emotions” (Rep.606d). According to Plato, emotions lead men to act irrationally and in a cowardly manner, especially citizens who become accustomed to poetry, particularly drama, which arouses the passions. Rather than analyzing the philosopher’s criticism of the value of theater and the expression of pain (such as lamentation and crying), I shall examine a contemporary case: the funeral of actor Jean-Paul Belmondo which was held by the French government amidst the SARSCoV-2 pandemic crisis. Through this approach I shall reassess the role of emotion in the education of citizens and the political strengthening of a city or a group.
Keywords: emotion; Republic; theater; rhetoric